2011
DOI: 10.1073/pnas.1113908108
|View full text |Cite
|
Sign up to set email alerts
|

Avenolide, a Streptomyces hormone controlling antibiotic production in Streptomyces avermitilis

Abstract: Gram-positive bacteria of the genus Streptomyces are industrially important microorganisms, producing >70% of commercially important antibiotics. The production of these compounds is often regulated by low-molecular-weight bacterial hormones called autoregulators. Although 60% of Streptomyces strains may use γ-butyrolactone–type molecules as autoregulators and some use furan-type molecules, little is known about the signaling molecules used to regulate antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 33 publications
3
146
0
2
Order By: Relevance
“…In contrast, the rAvaR1-ligand activities of the C10-epimer (19), the C4-epimer (22) and the 10-deoxy avenolide (28) demonstrated only one-half, one twenty-fifth and one hundredth of the activity of the natural product, respectively. 6 It can therefore be concluded that the stereochemistry at C4 and C10, and the presence of the hydroxyl group at C10, are important to the activity of avenolide as a rAvaR1 ligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the rAvaR1-ligand activities of the C10-epimer (19), the C4-epimer (22) and the 10-deoxy avenolide (28) demonstrated only one-half, one twenty-fifth and one hundredth of the activity of the natural product, respectively. 6 It can therefore be concluded that the stereochemistry at C4 and C10, and the presence of the hydroxyl group at C10, are important to the activity of avenolide as a rAvaR1 ligand.…”
Section: Resultsmentioning
confidence: 99%
“…6 Supplementary Information accompanies the paper on The Journal of Antibiotics website (http://www.nature.com/ja) Total synthesis and absolute configuration of avenolide…”
Section: Evaluation Of Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…PI factor enhances pimaricin production in S. natalensis (239). Avenolide is required at nanomolar concentrations for the onset of avermectin biosynthesis in S. avermitilis (238) (avenolide homologs are also found in S. fradiae, Streptomyces ghanaensis, and S. griseoauranticus).…”
Section: Control Of Five Extensively Studied S Coelicolor Antibioticmentioning
confidence: 99%
“…The single afsA family genes afsA, scbA, and avaA (17) are present on the genomes of S. griseus, S. coelicolor A3(2), and S. avermitilis, respectively. The flanking region of scbA has scbR (a receptor of an SCB1 autoregulator), and that of avaA has avaL1/L2 (receptors of an unidentified molecule), whereas the afsA locus is 3.9 Mb away from the locus of arpA (A-factor receptor gene).…”
Section: Discussionmentioning
confidence: 99%